Excellent cooking, worth a detour!: Dimensions of the overall experience offered by culinary arts - Brochado, F. O.; Loureiro, S. M. C. (Innovation, Knowledge, Judgment, and Decision-making as Virtuous Cycles: 7th Global Innovation and Knowledge Academy (GIKA) Conference Proceedings, 2017)
Luxury restaurants are expected to offer an outstanding culinary and gastronomic talent and expertise, to be authentic, creative and consistent and to provide quality and exciting food. In the twenty-first century, engaging in culinary art discourses involves a social dimension, and therefore social networking sites are used as resources for sharing gastronomic experiences with others and to read recommendations. User-generated restaurant reviews represent an interesting intersection of a participatory culture and foodie discourse. The main objective of this paper is to provide empirical findings by examining web-reviews in order to identify the expressive dimensions that describe the guests’ experience. A mixed-method content analysis is considered for this type of study, more precisely adopting a qualitative in-text interpretation as a supplement to the traditional quantitative word counts and factor analysis. A content analysis of reviews by guests on reviewing the top 3 Michelin awarded restaurants (2 stars) in Portugal produced a battery of concepts used to assess haute cuisine experiences from the guests’ perspective. The analysis produced a concept map encompassing the following dimensions food, restaurant, experience, menu, wine, special, view, beautiful, friendly, chef, visit, desert.